Pertumbuhan dan Hasil Gandum pada Berbagai Kerapatan Populasi dan Dosis Pemupukan Urea - Zubaidi, Akhmad; Anugrahwati, Dwi Ratna; Yakop, dan Uyek Malik (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Efforts to produce wheat in Indonesia need to be supported by the availability of cultivation technology suitable for agro-climate conditions in Indonesia, including the use of proper population density and fertilization dosages, which are fundamental for obtaining maximum yields. This study was aimed to determine ideal population density and dosage of urea for optimum grain yield of wheat in Lombok Island. The experiment carried out at Aik Bukak, Central Lombok at elevation of 400 m asl, to observe the growth and yield of two varieties of wheat, Nias and Gladius, with 4 plant population densities (133, 160, 200, and 250 plants m-2) and 3 dosages of urea fertilization, 200, 300, and 400 kg ha-1. Data from this study indicated that Lombok Island has the potential for growing wheat with quite dense population density of 250 plants m-2. This density yielded higher, 1.74 tons ha-2, due to the increased number of kernel per unit area without reducing individual kernel weight. The use of urea 300 kg ha-1 exhibited the best growth and yielded 1.32 tons ha-2.Keywords: fertilization, population density, wheat varieties